Polarization induced dielectric and electrical response of electrovector hydroxyapatite and ferroelectric sodium potassium niobate ceramics - Saxena A.; Kakimoto K.-I.; Dubey A.K. (My University, 2025)
The ability of hydroxyapatite (HA) to convert readily into an electret under low polarizing fields (1 kV cm-1) makes it as an excellent substitute for electro-active prosthetic implants. In the present study, compacts of electrovector HA and ferroelectric Na0.5K0.5NbO3 (NKN) were developed via the spark plasma sintering route. The compacts were then polarized at various polarizing fields of 30, 50, and 90 kV cm-1, respectively, at 150 C, for 1 h. Thereafter, samples were depolarized at heating rates of 1, 5, and 10 C min-1, respectively. The thermally stimulated depolarization current (TSDC) measurement reveals that the charge density in HA increases from ∼0.2 nC cm-2 to ∼2 µC cm-2 with an increase in the polarizing field from 30 to 90 kV cm-1. The dielectric (), as well as the ac conductivity behaviour of unpolarized and polarized (90 kV cm-1) HA, are compared. The activation energy is measured to be in the range of 0.6-0.7 eV, which is mainly associated with proton (H+) migration. For NKN, TSDC spectra reveal a slight shift in the phase transition temperatures (TO-T, TC) towards higher temperatures, with an increase in the polarizing field (30-90 kV cm-1) as well as the heating rate. The dielectric and ac conductivity measurements suggest that the polarization of NKN slightly decreases TO-T and TC, as compared to its unpolarized counterpart. The conductivity in NKN is mainly attributed to the migration of oxygen vacancies and n-type charge carriers. Furthermore, x-ray photoelectron spectroscopy analyses suggest that the polarization of HA at such a high field (90 kV cm-1) does not alter its surface chemistry. © 2020 IOP Publishing Ltd.